E-learning courseware for solving a fundamental system of linear equations by using gaussian elimination method / Sitinor Waheda Damri - Damri, Sitinor Waheda (2017)
Linear algebra is one of an important subject. This project is made to overcome students’ difficulties in understanding and solving system of linear equations fundamentally since they were too depending on their lecturers. The e-Learning Courseware for Solving System of Linear Equations provides the solution by using Gaussian Elimination method. The fundamental system of equations with matrices of size two by two are considered. The multimedia elements such as colors, interaction, graphic, audio and text also being considered, hence they can learn in an enjoy able way. In this project, ADDIE model consists of five phases is used. The use case diagram, flowcharts and interface is designed to meet the requirements. The development of this project was done with the aid of notepad and google chrome with64-bit operating system Windows 7. During implementation phase, the functionality testing is done to check whether all the buttons, links are functioning before distributed it to user. Usability testing was done in evaluation phase where users tested the completed application and gave their feedbacks through the questionnaire sheet. It is recommended that this application will be developed on mobile operating system supported by the multimedia elements such as animation and video for future enhancement.